2017
DOI: 10.14356/kona.2017001
|View full text |Cite
|
Sign up to set email alerts
|

Present Advancement in Production of Carbon Nanotubes and Their Derivatives from Industrial Waste with Promising Applications

Abstract: An increase in global consumption has led to an exponential increase in industrial production activities which inevitably results in overwhelming remain of industrial waste. Consequently it has driven increasing attentions of research and development teams in various countries to propose and investigate novel methodologies to utilize such industrial waste. Instead of using as alternative energy sources, usage of industrial waste for production of carbonaceous nanomaterials has been examined via various routes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 99 publications
(250 reference statements)
0
5
0
Order By: Relevance
“…Comprehensive reviews on synthesis of CNTs via pyrolysis and relevant methods have been provided by many researching teams, for instance, Kerdnawee et al 5) , Kumar The prime importance of this experimental investigation is set on understanding in dependence of characteristics and yield of CNTs on the weight ratio of ferrocene in a mixture of kerosene/ferrocene and preloaded ferrocene.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews on synthesis of CNTs via pyrolysis and relevant methods have been provided by many researching teams, for instance, Kerdnawee et al 5) , Kumar The prime importance of this experimental investigation is set on understanding in dependence of characteristics and yield of CNTs on the weight ratio of ferrocene in a mixture of kerosene/ferrocene and preloaded ferrocene.…”
Section: Introductionmentioning
confidence: 99%
“…[569,570] Instead of generating char as a low value or even undesirable byproduct, catalytic pyrolysis, hydrothermal treatments, and pyrolysis coupled with steam reforming transform plastic wastes into high-value-added functional carbonaceous (nano)materials such as carbon black, carbon nanotubes, graphene tuned for applications spanning energy storage materials, electrodes, carbon (nano)fillers, and absorbents for water purification. [571,572] In contrast to fast pyrolysis, the yield of carbonaceous char is higher for slow pyrolysis of PP. [573] Pyrolysis of waste tires yields oil and colloidal pyrolytic carbon, which are useful as rubber reinforcing agents.…”
Section: Open-loop Valorizationmentioning
confidence: 99%
“…Mohan et al [46], develop activated carbon from coconut shell for removal of pyridine derivatives. Kerdnawee et al [47] discussed the advancement of carbonaceous nanomaterial production from industrial waste in detail. This study enlightened several studies reported for synthesis of CNT using industrial waste such as -chemical process waste, petroleum refining process waste, plastic waste, automobile waste, because these wastes contains high amount of CH4, C 2 H 6 , C 2 H 4 , C 2 H 2 , CO, CH 3 OH and so on, would involve as carbon source for productions of carbonaceous material.…”
Section: Silica Based Alginate Bio-nanocompositementioning
confidence: 99%